HEPATOPROTECTIVE ACTIVITY OF COSTUS SPECIOSUS (KOEN. EX. RETZ.) AGAINST PARACETAMOL-INDUCED LIVER INJURY IN MICE - AlSaadi, Baiaan H.; AlHarbi, Shoaa H.; Ibrahim, Sabrin R. M.; El-Kholy, Amal A.; El-Agamy, Dina S.; Mohamed, Gamal A. (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Liver diseases are a common cause of mortality and morbidity over the world. It is caused mainly by toxic chemicals and chemotherapeutic agents. Costus speciosus (Koen ex. Retz.) (Zingiberaceae) is widely employed in various traditional medicines for the prevention and treatment of different aliments. The purpose of this study is to assess the protective effect of C. speciosus rhizomes MeOH extract against the injury of the liver induced by paracetamol (PA) in mice. Material and Methods: The mice were pretreated for seven days with distilled H2O, silymarin 12 mg/kg or 100 and 200 mg/kg MeOH extract. Then, PA (750 mg/kg) was also intra-peritoneal administrated once a day. Animals were euthanatized 24 h after the damage inducement. The levels of the serum enzymes aspartate aminotransferase (AST), alkaline phosphatase (ALP), alanine aminotransferase (ALT), and aspartate aminotransferase, in addition to the tumor necrosis factor-alpha (TNF-α), were determined. Moreover, the histopathological examination was carried out. Results: Administration of the MeOH extract (200 mg/kg) showed improvement in the toxic effects of PA through significant fall on the serum markers enzymes of liver damage: AST, ALT, and ALP, as well as TNF-α, compared to silymarin. In parallel, the histopathological profile in the mice` liver also proved that extract markedly minimized the PA toxicity and maintained the liver tissues` histoarchitecture to near the normal ones more than that achieved by silymarin. Conclusion: The findings suggested that C. speciosus extract acts as a potential hepatoprotective agent against PA-induced liver toxicity. This hepato-protection effect may be due to the existence of steroids, saponins, different glycosides, and phenolic compounds in C. speciosus.